Persepsi Mahasiswa dan Dosen terhadap Early Clinical Experience pada Program SI Keperawatan STIK Immanuel Bandung - Yuliana Yuliana; Ova Emilia; Gandes Retno Rahayu (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2012)
Background: Early Clinical Experiences (ECEs) is a learning strategy that helps students integrate their knowledge through clinical learning in classes easily from their initial semester of study. Advantages have been earned by both students and lecturers; nevertheless, obstacles in the implementation have frequently emerged. Ideally, lecturers and students should know their own perception on ECEs for the sake of creating good communication and expected learning results in order to improve preclinical education. The purpose of this study is to find out different perceptions between students and lecturers on ECEs in nursing undergraduate program.Method: This was a descriptive study using quantitative and qualitative approaches (mix method). Subjects comprised students in the year of 2007 and 2008 as many as 71 nursing students and 21 lecturers, consisting of 11 academic advisors and 10 clinical advisors. Qualitative method was done with Focus Group Discussion for students groups and in-depth interview to academic advisors and clinical advisors. Quantitative analysis used descriptive analysis and comparative analysis used One Way Anova analysis. Qualitative analysis used content analysis that included identification, coding, categorization, and synthesis. In the end, the result of quantitative analysis was integrated with the result of qualitative analysis.Results: Mean score of students’ perception on ECEs was 3.11 (SD 0.24) which was lower than that of academic advisors (3.27 (SD 0.28)) and of clinical advisors (3.30 (SD 0.25)), (F score of 3.18 and p<0.05) while the result of multiple comparison test of students and clinical advisors showed p=0.047. Perception difference of students and clinical advisors on ECEs components in the supervision process showed p=0.00.Conclusion: There was a significant difference among three respondent groups on ECEs perceptions. The significant difference between students and clinical advisors was in the component of supervision process while there was no significant difference between students and academic advisors as well as between academic advisors and clinical advisors. Students posed the lowest ECEs perception score compared to both academic and clinical advisors. Problems came up in the components of structure and content, supervision process, learning experience, and student evaluation.